An assessment and perception of the hazards of pesticide use in the aquatic environment. (4th August 2014) - Burridge, L. E.; Haya, K.; Zitko, V.
Various models are available to help assess the risk of chemicals to the aquatic environment. The hazard posed by pesticides in use in Prince Edward Island, Canada was estimated by a model based on fugacity. Groups of individuals currently working in the field of aquatic toxicology were asked to rank 20 of these pesticides in order of decreasing hazard. There is little agreement between prediction using the model and perceptions of the respondents. There is general agreement between two of the groups of toxicologists surveyed, although this is also variable. The results show a need for standardised methods of hazard assessment.